A study of relationship between sinus diseases and lower respiratory tract infections - Hans, Manseerat; Gill, Kushal Deep; Bhagat, Sanjeev; Ratti, Jasmine; Goel, Khushboo (GMC Patiala Journal of Research and Medical Education, 2022)
Background - To find out the association between sinus diseases with lower respiratory tract infections. Methods – The study was conducted on 100 patients, 59 cases with diagnosis of sinusitis were assigned group I, 41 cases with diagnosis of LRTI were assigned group II. All clinical and radiological characteristics were recorded, incidence of sinusitis in various lower respiratory tract infections was studied. Patients diagnosed with sinobronchial syndrome were divided in control and study group, study group was given medical treatment for sinusitis for 15 days. All patients were followed for 3 months. Subjective and objective improvement /worsening of LRTI in both study and control group was recorded. Results – Out of 18 cases of bronchial asthma, 9 (50%) had coexisting sinusitis. Incidence of sinusitis in bronchiectasis patients was 50%. 11 out of 19 cases of chronic bronchitis had sinusitis (57.89%). It was also observed improvement in lower respiratory tract symptoms was more in study group than in control group ,i.e., 57.14% versus 5.55% on first follow up, 71.43% versus 11.11% on second follow up. Conclusions- Paranasal sinusitis has been diagnosed frequently in patients who have lower respiratory tract infections and is important precipitating factor in provoking lower respiratory tract infections. Hence there should be a team approach between chest physician and otolaryngologic surgeon and any patient suffering from disease of either airway should be regarded as suffering from ‘Single airway disease’